Deciphering heat stress tolerance for grain yield in bread wheat genotypes under the semi-arid region of Rajasthan - Priyesh Verma; S.S. Punia (Annals of Agricultural Research, 2025)
Heat stress is a major abiotic constraint limiting wheat (Triticum aestivum L.) productivity, particularly in regions experiencing rising temperatures due to climate change. Our breeding program’s ultimate goal is to develop thermal stress-tolerant cultivars and the realisation of the potential for yield in hot climates. In light of the above, the study was conducted in three environments, i.e. early, normal and late sown conditions with 18 diverse genotypes and their 45 F1’s to magnify the yield level of wheat in high temperature areas by selecting stress-tolerant parents and cross combinations. Based on the HSI values, the genotypes were classified into four different categories, i.e. highly heat tolerant (HSI <0.50), heat tolerant (HSI: 0.51-0.75), moderately heat tolerant (HSI: 0.76-1.00), and heat susceptible (HSI >1.00). An overall assessment revealed that the parents HD 3086, WH 1081, RAJ 1482, HI 1563; and the crosses HI 1563 x RAJ 4238, RAJ 1482 x RAJ 4238, RAJ 4079 x HTWYT 37, WH 1142 x F1, WH 1081 x F1 and HI 1563 x F1 were identified as desirable for most of the yield associated traits as they displayed maximum tolerance under heat stress conditions.